The euro - what'sin it for me : an economic analysis of the Swedish euro referendum of 2003 - Jonung, Lars.; Vlachos, Jonas; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
The Swedish referendum on the euro in September 2003 is an exceptional event for researchers of monetary unions and of European economic integration. Voters chose between maintaining the domestic currency, the krona, and replacing it with the euro, the single currency of the European Union. The referendum revealed significant dividing lines between Yes- and No-voters in areas such as income, education, sex, employment, geographical location and industrial structure. The aim of this study is to explain the large differences in voting behaviour. The empirical analysis of the referendum outcome is based on the traditional optimum currency area (OCA) approach, merged with an account of the distributional effects of Swedish membership of the euro area as they were perceived by the voters. The OCA approach builds upon the trade-off between reducing transaction costs by entering a monetary union, thus increasing trade and income, and obtaining macroeconomic insurance by having a domestic currency with a flexible exchange rate. This trade-off was perceived differently by voters depending on their evaluations of the costs or risks and the benefits or gains of adopting the euro versus keeping the krona, the domestic currency. We use the OCA approach to generate a set of hypotheses concerning voting behaviour that are explored in our econometric tests based on exit polls covering more than 10,000 voters on the day of the euro referendum. Our econometric results suggest that the OCA approach has strong predictive power when explaining differences in voting behaviour across groups in society. In particular, we demonstrate that insurance considerations dominated the prospect of reduced transaction costs in the referendum. It did so in a systematic way across segments of society indicating that voters were capable of making rational comparisons of the costs and benefits of monetary unification. Voters asked themselves: The euro - what's in it for me? Then they voted accordingly.
Economic Papers